Antimicrobial activity of novel chalcones and modulation of virulence factors in hospital strains of Acinetobacter baumannii and Pseudomonas aeruginosa. (June 2019) - Ušjak, Dušan; Ivković, Branka; Božić, Dragana D.; Bošković, Lidija; Milenković, Marina
Abstract: Acinetobacter baumannii and Pseudomonas aeruginosa are frequent multiresistant nosocomial pathogens that cause wound and pulmonary infections in hospitalized patients. As being increasingly resistant to most clinically available antibiotics, there is a constant need for exploration of new substances that could kill them or inhibit their growth, or alternatively inhibit some of their essential virulence factors. Chalcones are chemical compounds with well-documented antimicrobial potential. The aim of this study was to examine effectiveness of four newly-synthesized chalcones against the multiresistant clinical strains of A. baumannii and P. aeruginosa . Antibacterial activity of chalcones was investigated with broth-microdilution test and time-dependent killing assay. Synergistic effects of tested compounds with antibiotics (meropenem, amikacin and ciprofloxacin) were determined by checkerboard assay. The effects of chalcones on expression of virulence factors in P. aeruginosa (pyocyanin production, swimming and swarming motility) and A. baumannii (twitching and surface-associated motility), along with their biofilm production, were also examined. The obtained results indicate substantial antimicrobial activity of the tested chalcones (MICs = 100–175 μg/mL) and several synergistic interactions with antibiotics, as well as notable reduction in expression of all investigated virulence factors. These promising results may constitute a good basis for further research. Highlights: Novel chalcones inhibit growth of A. baumannii and P. aeruginosa at concentrations of 100–175 μg/mL. Tested chalcones yield 41.67% of synergistic interactions with meropenem, when tested against A. baumannii. All of the chalcones significantly inhibit pyocyanin production, swarming and swimming motility of P. aeruginosa. The p-CF3 chalcone notably inhibits A. baumannii twitching and surface-associated motility. Biofilm production of A. baumannii and P. aeruginosa was mostly reduced by p-CF3 (56.85%) and o-OCH3 (57.02%), respectively.